A comparative study on mothers' and teachers' evaluation of behavior problems of children attending preschool education [Okul öncesi eǧitim alan çocuklarin davraniş problemlerinin anne ve öǧretmen deǧerlendirilmeleri açisindan karşilaştirilmasi] - (:unkn) unknown (My University, 2008)
This study aims to make a comparative analysis of families' and teachers' evaluation of behavior problems among children at the age of six, receiving preschool education. The data of the study were collected from the mothers and teachers of 60 male and 61 female children. Data collection instruments are Child Behavior Checklist for Ages 4-18 (CBCL/4-18) and Teacher Report Form (TRF/5-18).The correlations between mothers and teachers in the subtests of Child Behavior Checklist and Teacher Report Form show that the relationship is of low and intermediate significance (r=0.183 r= 0.355, p<0.05). The correlation coefficient is higher for externalizing problems (r=0.361), compared to internalizing problems (r=0.238). The relationship is of intermediate significance for the problems as a whole (r=0.298, p<0.05). The findings were analyzed by the sex and socioeconomic status of children as well as by the educational level of their parents.In this study it was shown that behaviour problem, in children coud not be evaluated with the information caring out from only one source. It was found out that some behaviour, that can be perceived by mothers as a problematicmight be not regarded as a problem by teachers. Sometimes the opposite situation is also possible. So the view and opinion of teachers having interactions with children should be regarded in studying related child behaviours.
Keywords: Child behaviour checklist(cbcl/4-18, trf/5-18); Parent; Preschool; Teacher